The Case of Radclyffe Hall’s The Well of Loneliness - Brian James Baer; Yingmei Liu (TranscUlturAl, 2022)
This article explores the notion of queering translation in relation to Radclyffe Hall's The Well of Loneliness (1928), often described as the first lesbian novel, focusing on two key terms related to sexual identity, the word queer, which was semantically unstable at this historical moment, and the quasi-scientific term invert. Hall's provocative use of queer against the minoritizing invert, which presages queer critiques of identitarian politics by several decades, complicates the field of sexuality in the novel, presenting special challenges for translators. Those challenges are analyzed in the early French translation of the novel and in later Chinese translations, from both Taiwan and mainland China.